Alteration of cholinergic pressor and antinociceptive responses in rats pretreated with the cholinergic toxin AF64A - (:unkn) unknown (ELSEVIER SCIENCE INC, 1998)
1. In the present study, the presser and antinociceptive effects of physostigmine and oxotremorine were investigated in rats injected with AF64A intracerebroventricularly. 2. Physostigmine (50-100 mu g/kg, IV)-induced presser responses were significantly lower in AF64A-injected rats compared with saline injected animals, whereas oxotremorine (20-80 mu g/kg, IV) induced responses were found to be similar to those seen in the saline group. 3. The physostigmine (100 mu g/kg, SC)-induced antinociceptive effect was totally abolished by AF64A treatment, but that of oxotremorine (30 mu g/kg, SC) remained unchanged at the tail-flick test. 4. The results of this study present functional evidence for AF64A-produced substantial loss of cholinergic neurons involved in the regulation of blood pressure and nociception but not in postsynaptic muscarinic receptors. (C) 1998 Elsevier Science Inc.
Keywords: cholinergic control; blood pressure; antinociception; AF64A; Alzheimer's disease; physostigmine; oxotremorine; INTRAVENTRICULARLY ADMINISTERED ACETYLCHOLINE; MUSCARINIC RECEPTOR SUBTYPES; CENTRAL NERVOUS-SYSTEM; BLOOD-PRESSURE; HYPERTENSIVE RESPONSE; PASSIVE-AVOIDANCE; CENTRAL CARBACHOL; NEUROTOXIN AF64A; PHYSOSTIGMINE; STIMULATION